Positive Effects of Extra-Virgin Olive Oil Supplementation and DietBra on Inflammation and Glycemic Profiles in Adults With Type 2 Diabetes and Class II/III Obesity: A Randomized Clinical Trial - Silveira, Erika Aparecida; Rosa, Lorena Pereira de Souza; de Resende, Danilo Pires; Rodrigues, Ana Paula dos Santos; da Costa, Adeliane Castro; Rezende, Andréa Toledo de Oliveira; Noll, Matias; de Oliveira, Cesar; Junqueira-Kipnis, Ana Paula (Frontiers in Endocrinology, 2022)
Background Evidence on the effects of dietary interventions on inflammatory markers in individuals with obesity and type 2 diabetes mellitus (T2DM) is scarce. Our study evaluated the effects of extra-virgin olive oil alone and in combination with a traditional Brazilian diet on inflammatory markers and glycemic profiles in adults with both T2DM and class II/III obesity. Methods Adults aged 18-64 years with T2DM and class II/III obesity were randomized into two intervention groups: 1) extra-virgin olive oil only and 2) extra-virgin olive oil + a traditional Brazilian diet (OliveOil+DietBra). Data on sociodemographic characteristics, lifestyle, anthropometry, biochemical markers and inflammatory markers were collected. The primary outcomes were glycemic parameters and inflammatory markers. The body mass index (BMI) and weight were the secondary outcomes. Results Forty individuals with T2DM and class II/III obesity were enrolled, and 34 (85%) completed the intervention course. The intake of olive oil was 37.88 ± 12.50 mL/day in the olive oil group and 37.71 ± 12.23 mL/day in the OliveOil+DietBra group, with no significant difference between groups (p = 0.484). Compared to the olive oil only group, the OliveOil+DietBra group had significantly lower levels of fasting insulin (p = 0.047) at the end of the intervention, whereas the other glycemic parameters were not altered. In the OliveOil+DietBra group, serum levels of inflammatory cytokines, IL-1α (p = 0.006) and adiponectin (p = 0.049) were lower and those of TNFα were higher (p = 0.037). There was a significant reduction in BMI and weight compared to the baseline values in the OliveOil+DietBra group (p = 0.015). Conclusions The intervention with OliveOil+DietBra effectively decreased the levels of fasting insulin, IL-1α and adiponectin, suggesting its beneficial role in improving the inflammatory profiles and fasting insulin levels in adults with class II/III obesity and T2DM. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT02463435